Reducing sick leave, improving work ability, and quality of life in patients with mild to moderate Long COVID through psychosocial, physiotherapeutic, and nutritive supportive digital intervention (MiLoCoDaS): study protocol for a randomized controlled trial - Krotz, Adrian; Sosnowsky-Waschek, Nadia; Bechtel, Stephanie; Neumann, Christine; Lohkamp, Monika; Kovacs, Gabor; Genser, Bernd; Fischer, Joachim E. (Trials, 2023)
Following SARS-CoV-2 infection, a relevant proportion of patients suffer from persistent or recurring sequela, even after initially mild primary illness. Many patients experience exhaustion and fatigue, rendering them incapable of working. Long COVID exerts a substantial burden on society and the healthcare system: at least 65 million people are currently affected worldwide. The underlying pathobiology is a complex derangement in several organ systems. To date, causal pharmaceutical therapies remain elusive. Waiting lists for specialist care are long. Rapidly scalable digital interventions offering support for the frequent subgroup of patients with mild to moderate impairment from Long COVID are urgently needed. The MiLoCoDaS study compares three intensities of a potentially rapidly scalable digital intervention aiming to accelerate recovery. The overall objective is to figure out if there is a difference in the effect sizes between these modalities. The online intervention uses a learning platform (LMS, TYPO3 framework) comprising 12 sessions of medical, psychological, physiotherapeutic, and nutritional content. The three modalities differ as follows: patient information only (sham intervention, control), information plus interactive digital workbook including practical exercises (digital intervention), and the digital workbook augmented by once-weekly online seminars and discussion groups (person and peer-contact). Eligible patients are 18-67 years old satisfying Long COVID diagnostic criteria. Patients are recruited through primary care physicians and randomly allocated. The primary endpoint is the number of sick leave days during the 6-month observation period; secondary endpoints are patient-reported symptoms, quality of life, and work ability. The study size provides a power of 80% at a type I error of < 0.05 to show an effect size of Cohen = 0.3 between the augmented and the sham intervention (N = 152 per arm, total accounting for attrition N = 600). If one of the two interventions is superior to providing information alone, MiLoCoDaS would provide the starting point for a rapidly scalable digital intervention for the frequent and currently underserved patient group with mild to moderate impairment from Long COVID. Several caveats pertain to the heterogeneity of Long COVID manifestation and duration prior to inclusion. It is conceivable that the possible effect of the intervention may differ across subgroups. Therefore, a priori defined secondary analysis will be conducted. German Clinical Trials Register (DRKS) DRKS00028964. Registered on 24 August 2022.
Gesehen am 15.04.2024